An interactive mobile news reporting application / Mohammed Ali Ahmed Al-Sharafi - Mohammed Ali Ahmed , Al-Sharafi (2017)
Working outside the office increases the challenges for mobile workers to perform their jobs efficiently. One of the mobile workers is Mobile Journalist Reporter (MJR) who is the ultimate target of this research. As part of their works, several MJR works outside of the newsroom to attend press conferences, special events, and other activities that require their presence to collect news contents and prepare a report to be sent to the newsroom. Using mobile devices, the Mobile News Reporting (MNR) is an important aspect that needs to be given much attention to enable the news contents to be sent quickly and efficiently. Currently, most of the research directions are focusing on how to improve upon giving updated news to followers’ audience using mobile technology. However, there is a limited attention paid for improving the other side of mobile news technology, which is related to journalists’ task regarding delivering news content from event site to Newsroom Journalist Editor (NJE) using mobile devices. In addition, there are some news organizations, which still use traditional methods to deliver news contents such as using email, fax, chatting apps, or social networks. These leads to a delay in news contents processing and delivering, duplicated tasks, unorganized data, and human mistakes of files archive. In line with the demands of MJR to adopt the latest technologies and new methods of news contents delivery, there is a need to improve the overall MNR approach. A number of researches were conducted to investigate the process of MNR and to support the future development towards mobile solutions for improving and enhancing MNR challenges. Some of these challenges are: 1) sending news contents photos and videos instantly without control, enough details, and guide from the newsroom; 2) almost no acknowledgement and notification mechanism between MJR and NJE are provided; 3) either available as only web version such as CNN iReport web application or mobile version such as Ana Ara mobile application with same problems in first and second points; and 4) in some approaches, there is no usability support by citizen journalist reporters. The aim of this study is to improve and enhance news contents delivering method for daily news coverage to increase the productivity and efficiency through proposing and designing a hybrid interactive approach of mobile & web application using Mobile Cloud Computing (MCC) technology and to be evaluated by professional journalists. As a result, the outcome of proposed approach implement the requirements and features needed for new mobile news reporting application known as i-MNReport which can support citizen MJR. The proposed approach subjected to professional journalists’ evaluation. The overall assessment accepted the proposed approach with recommendations to add more features that can be considered in future development. Consequently, the proposed approach showed that it increases the productivity and efficiency of mobile news reporting system.